Current state and prospects of the development of Lviv region balneological resorts - Starynets, Olena (Збірник наукових праць Черкаського державного технологічного університету. Серія: Економічні науки, 2015)
The paper presents the analysis of current state of the development of balneological resorts of Lviv region (Truskavets, Morshyn, Skhidnytsya) and assessment of the future prospects of their economic development at the present stage. It is shown that the problem of the analysis of the status and prospects of health resort industry is one of the most relevant in the context of building the socially oriented market economy in our country. The paper highlights the role of state authorities in this mechanism, which is to create favourable conditions for activity in the tourism and recreation sector, which will create mechanisms for investments of both large-scale and small projects. Capacity building of tourist-recreational infrastructure by attracting domestic and foreign investment is one of the priorities of socio-economic and cultural development of Lviv region.